INOVASI BERKELANJUTAN: PENGENALAN DAN PENDAMPINGAN PEMBUATAN ECOBRICK SEBAGAI ALTERNATIF PENGELOLAAN SAMPAH PLASTIK DI SDN 002 RAMBAH - Radjawaly Usman Rery; Rifky Ananda; Muhammad Ilham Daprius; Hari Andika; Teddy Wira yudha; Vinny Maulina Marten; Hikmah Salamah Huriyah; Nadya Feroza Mardhatillah; Anggun Siti Karomah9; Nurul Aini Nasution; Frena Maisa Putri (Bajang Institute, 2023)
This journal aims to examine the production of ecobricks as an alternative in managing plastic waste. Ecobrick is a technique of plastic waste management that involves using empty plastic bottles filled with various types of plastic waste until they are tightly compacted. Ecobricks are considered as an effective approach in dealing with plastic waste, particularly in school settings. The production of ecobricks requires used plastic bottles as containers, plastic waste as filling material, iron frames, and wood for compacting the plastic content. In this service activity, socialization and ecobrick production were conducted in one of the schools in Rambah Tengah Utara Village, namely SDN 002 Rambah. Through this activity, it is expected to raise environmental awareness among the community, thereby reducing the impact of waste pollution and benefiting the surrounding society.